GEOGRAPHY OF THE USA AND ITS POPULATION. - Adurakhmanov Turakhon Saydullayevich,; Abdumutalibova Kibriyo, (TADQIQOTLAR, 2025)
Annotation. This article explores the diverse geography of the United States and its  impact  on  population  distribution  and  demographics.  It  examines  the  country's major physical regions, including mountains, plains, rivers, and coastal areas, and discusses  how  these  features  have  influenced  human  settlement  and  economic development. The article also analyzes population trends, urbanization, and migration patterns, highlighting the differences between rural and urban areas across various states. Special attention is given to demographic changes, such as population growth, density, and regional shifts, providing a comprehensive overview of the relationship between geography and population in the USA.